Gregarious Flowering in Dendrocalamus stritus in Shahdol (Madhya Pradesh)-some Management Considerations - Dwivedi, A. P. (Indian Forester, 1988)
Gregarious flowering in Dendrocalamus stritus is recognised phenomenon which occurs periodically after a period of 25 to 100 year. The periodicity and intensity of flowering depends upon age of clumps, site factors, location, management pratices and biotic interferences. Gregarious flowring in bamboo occurred in Shahdol Circle (Madhya Pradesh) during 1984-87 where the author worked as Conservator of Forests Observation on the intensity of gregarious flowering is found to he associated with age, site quality, management practices and biotic interferences. Certain management considerations necessilated due to gregarious flowering such as; seed collection, rescheduling felling operation, protection of the area, creation of rhizome bank and artificial regeneration, etc. are discussed in this paper.